Instructional Design to Promote Translingual Practices in an English First Additional Language Context - Zano, Kufakunesu; Mbirimi-Hungwe, Vimbai (JOLLT Journal of Languages and Language Teaching, 2023)
Languages are not set, autonomous, bounded entities whose nature cannot be disrupted; they are flexible entities that can be reformed, re-arranged and recreated to fit into new contexts of communication. This study was driven by the need to explore the instructional design used to promote translingual practices in an English first additional language context in the Further Education and Training phase. For this qualitative study, eight (8) English first additional language teachers in the Further Education and Training phase were used as respondents. These teachers were stationed at four (4) high schools in one district of South Africa, meaning two (2) teachers per school were selected. The researchers used telephone interviews to collect data. The results revealed that translanguaging can be used in conjunction with collaborative activities like co-teaching, peer tutoring and group work in the English first additional language classroom. Â Besides, all learners have prior knowledge gained from schooling and life experiences and English first additional language teachers can build on those experiences. Also, based on the findings, it is indispensable to take advantage of modern technological facilities like WhatsApp in aiding the task of teaching English first additional language.